An Audit Report on Bacterial Meningintis among Children Admitted at Muhimbili National Hospital, Dar es Salaam, Tanzania (Tanzania Medical Journal, 2007)
Background: This is a preliminary report of the ongoing paediatric bacterial meningitis surveillance at Muhimbili National Hospital, Dar es Salaam, Tanzania. The World Health Organization (WHO AFRO) introduced this initiative to countries in the African region. The report covers the period beginning October 2001 up to December 2004.Methodology: All patients suspected to have acute bacterial meningitis were registered and a sample of cerebral spinal fluid (CSF) was taken from each patient and subjected to standard laboratory investigations. Results: A total of 16350 children were admitted during this period and, out of these, 1529 (9.6%) were suspected to have bacterial meningitis. CSF was collected from 84% of the children suspected of suffering from bacterial meningitis. While Bacteria were isolated from 5.6% of these samples, bacteria isolation rate from turbid CSF(96 samples) was 72.9%. The commonest isolates were Klebsiella species (26%), Streptococcus pneumoniae (22%), Haemophilus influenzae (13%), Salmonella species (9.1%) and E. coli (6.5%). N. meningitidis was not isolated during the three year period. Of all children with suspected bacterial meningitis, 61% were in the first 12 months of life while 3.8% of them were aged 36 months and above. H. influenzae was not observed to cause disease after the age of three years while Streptococcus pneumoniae continued to cause disease up to the age of 60 months (5years). Whereas Klebsiela spp, S. pneumoniae and H. influenzae contributed to 22.5% death rate each to the total meningitis death burden, H. influenzae had the highest microbial agent-specific mortality rate (90%), followed by E. coli (80%), and Salmonella spp. (66%). About 52.5% of the deaths occurred in the first 5 months of life and the overall disease case mortality rate was 51.9%.Conclusion: The low bacteria isolation rate could be attributed to the prior use of antibiotics and the use of human blood agar instead of sheep's blood agar for the isolation of H. influenzae. The high frequency of Klebsiella spp causing meningitis has not been frequently reported in Africa. The results of this study further confirm that there is no consistent pattern of microorganisms causing meningitis in tropical Africa. Recommendation: The high mortality rate observed in this study supports the need to introduce the H. influenzae and S. pneumoniae vaccines in our routine immunization schedules. There is a necessity of looking for factors contributing to this high death rate.Tanzania Medical Journal Vol. 22 (1) 2007: pp. 5-8